EDUCATION AND THE ATTITUDE OF RESPECT FOR NATURE - Maxwell Borjor Achuk Eba (Universitas PGRI Madiun, 2021)
This work addresses the question: How is respect for nature to be learned? In this aspect, we bring the perspective of virtue ethics. To be respectful towards nature is to develop a certain attitude within us. This attitude can be inculcated among human beings through relevant education. Proper education will build up a new awareness showing the need for being respectful towards nature. Environmental laws have been enacted by governments to help solve the environmental crisis. Yet it is true that the environment can be protected through these laws but it cannot be done fully. We conserve our environment out of fear of punishment. This is the main reason why our environmental laws fail. It is through moral awareness and action it can be done in a better way. Hence ultimately education can provide an important insight in our dealing with the environment. Hence education plays a major role in restoring environmental crisis. Man’s attitude towards nature depends on the type of education he receives. This work argues that, through education, we can cultivate an attitude of respect towards nature. This will enable us to see in what way the attitude of respect for nature could be an instrument for the protection of nature. In this connection, we have taken help from O.P Dwivedi’s idea of basic principles and environmental codes on the basis of which, as he argues that environment can be better preserved. He has also suggested certain guiding principles for environmental management. Hence with these principles, human beings can become good stewards of nature with the attitude of respect for nature.